PENGARUH MEDIA BOOKLET TERHADAP PENGETAHUAN GIZI IBU DALAM MENGHADAPI MASA NIFAS DI KLINIK FERAWATI S.ST. PALEMBANG TAHUN 2024 - Italia; Arlina, Zakinah; Salama (Jurnal Kesehatan dan Pembangunan, 2025)
Issues related to nutritional consumption levels are influenced by several dominant factors, such as education, occupation, food taboo culture, and body image. Data from the World Health Organization (WHO) in 2016 showed that nutritional needs during the postpartum period, especially during breastfeeding, increased by 25%. This research method applies a quantitative analytical approach with a cross-sectional design. The population in this study included all pregnant women who were at the Ferawati S.ST Palembang midwife clinic in November with a total sample of 25 respondents. The results of the study showed a significant relationship between pregnant women's knowledge regarding the influence of booklet media on maternal nutritional knowledge during the postpartum period at the Ferawati Midwife Clinic, S.ST Palembang in 2024 with a P-value = 0.00. It is hoped that the Health staff at the Ferawati Midwife Clinic, S.ST Palembang can be more optimal in increasing pregnant women's understanding of maternal nutrition during the postpartum period, so that it can be a guideline for improving the quality of health services and quality at the research location.